Cultura postmaterialista y variaciones en el espiritu emprendedor - Maria José Pinillos Costa (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
The aim of this paper is to explore whether postmaterialism explains differences in Total entrepreneurial-activity rates across Spanish Autonomous Communities. A distinction is made between potential entrepreneurs, nascent entrepreneurship, new business formation and Established business, as defined within the Global Entrepreneurship Monitor (GEM). The measure for postmaterialism is based upon Inglehart's four-item postmaterialism index. A set of economic, demographic and social factors is included to identify the independent role postmaterialism plays in predicting entrepreneurial activity levels. Findings confirm the significance of postmaterialism in predicting total entrepreneurial activity and its importance varies depending on the stage of business creation considered (conception, birth or residence).
Keywords: P52; Z1; M13; O11; O57; 330; entrepreneurship; cultural values; self-employment; potential entrepreneurs; new companies